A Review of the External Processes Related to Assessing Quality of New Undergraduate Academic Programming in Canadian Universities - Kotsopoulos, Donna; McKee, Joanne; Goebel, Tina; Dickson, Brandon; Groen, Jovan; Savas, Renee; Nitsotolis, Jasmine (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
Quality assurance (QA) processes oversee programmatic creation and cyclical reviews to ensure the quality of academic programming for students. In Canada, university oversight, including funding and QA, takes place at the provincial level. Oversight of quality varies dramatically across regions in Canada, from government ministries to arm’s-length quality assurance agencies to internal university governance. Our research compares the guiding documents of Canadian QA agencies from across Canada to answer the questions: (1) How do external QA procedures vary in provinces across Canada, and (2) Is financial viability considered in QA? Our results suggest a distinct lack of specificity in multiple areas, most profoundly in the financial considerations. Consequently, in the fifth section, and based on our findings, we propose a Financial Viability and Sustainability Framework for Quality Assurance (FVSF-QA) as a tool for supporting consideration of financial viability and stability in quality assurance.